Return Saham Kaitannya Dengan Profitabilitas Pada Perusahaan Subsektor Pulp Dan Kertas - Riantono, Yulio Widi; Tarmedi, Eded; Mayasari, Mayasari (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2017)
The purpose of this study was to determine the effect of profitability on stock returns on pulp and paper subsector companies. This research was conducted in a span of more than one year, so the research design used was time series design. This study uses a descriptive and verification approach with time series design methods. A total of 5 companies were selected as samples using purposive sampling. Financial statements and stock data are used as research instruments in retrieving data, and data analysis techniques used are simple linear regression. Based on the research findings it can be seen that profitability has a significant effect on stock returns. Differences in this study were found in the objects and methods of research, population and research samples, period of research, measurement tools and results of research, and sources of theory.